A permissioned decentralized blockchain-based mobile banking system with privacy and security - Ansary, A. A. Noman; Jim, Syed Nur.A.Rabbi; Labeeba, Lamya; Hasan, Kashfia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.